THE SYNONYMY OF HIPPOLOGICAL TERMS IN THE LEXICAL-SEMANTIC SYSTEM OF THE ENGLISH LANGUAGE (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article is devoted to the synonymy of hippological terminology in the lexico-semantic system of English with some samples which belong to horse term for equine behavior.